Reimaging Indigenous Baduy Women in the Vortex of Digital Technology: Female Empowerment Perspective - Setijadi, Naniek Novijanti (JURNAL KOMUNIKASI INDONESIA, 2023)
Baduy is a tribe that adheres to ancestral traditions, a social system based on cultural values, beliefs, and rules passed down for generations. Nevertheless, they are now touched by digitalization. This study considers challenges, difficulties, and potential advantages when communities, especially women in remote, rural, non-electrified homes, are equipped with fundamental communication technology knowledge and competence. It aims to identify critical factors and trends of indigenous Baduy women's participation in ICT and examines the practices enabling women's participation in social media. Primary data of research is the result of observation and in-depth interviews, while secondary data is the result of documentation. This research is based on the theory of technology domestication, which emphasizes the role of users in making media technology usable in their daily context. The empirical and qualitative fieldwork data results reveal how indigenous Baduy women construct their sense of reality in the vortex of digital transformation while struggling to maintain their traditional culture. Findings are presented with a discussion of the implications and challenges for new media uses as a means of cultural production for alternative, more socially oriented purposes.